2021
DOI: 10.1186/s40517-021-00195-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical zonation of rock properties and the development of fluid migration pathways: implications for enhanced geothermal systems in sedimentary-hosted geothermal reservoirs

Abstract: Oil and gas operations in sedimentary basins have revealed the occurrence of significant temperature anomalies at depth, raising the possibility of major geothermal resource potential in the sedimentary sequences. The efficient development of such a resource may require enhancement by hydraulic stimulation. However, effective stimulation relies on an initial assessment of in situ mechanical properties and a model of the rock response. Here, we examine the distribution of mechanical properties (unconfined compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Previous field observations, experimental, and numerical studies have demonstrated that fractures propagating from a stiff interval towards a less-stiff one tend to propagate more efficiently and commonly penetrate the contacts (Laubach et al 2009;Gudmundsson et al 2010;Slatt and Abousleiman 2011;Ferrill et al 2014;Galvis et al 2018;Kolawole et al 2021b). These suggest that induced fractures from target lithofacies characterized by low aspect ratios, and stiffer rocks with higher bulk and shear modulus, will tend to generate a coherent and connected fracture network that can connect with other pre-existing natural fractures or reactivate faults.…”
Section: Implications For Fluid Flow In Bakken Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous field observations, experimental, and numerical studies have demonstrated that fractures propagating from a stiff interval towards a less-stiff one tend to propagate more efficiently and commonly penetrate the contacts (Laubach et al 2009;Gudmundsson et al 2010;Slatt and Abousleiman 2011;Ferrill et al 2014;Galvis et al 2018;Kolawole et al 2021b). These suggest that induced fractures from target lithofacies characterized by low aspect ratios, and stiffer rocks with higher bulk and shear modulus, will tend to generate a coherent and connected fracture network that can connect with other pre-existing natural fractures or reactivate faults.…”
Section: Implications For Fluid Flow In Bakken Formationmentioning
confidence: 99%
“…This phenomenon is caused by the way these pores are shaped; cracks are weaker than intragranular pores, which are known as stiff pores, and as the pore spaces increase, this stiffness difference becomes more pronounced. Regarding the susceptibility of rocks to faulting and fracture, the seismic velocities (V p and V s values) are extremely important (Kolawole et al , 2021b. Therefore, fracturing and faulting are strongly associated with pores that have a low aspect ratio (0.01 and 0.05).…”
Section: Predicted Fractomechanical Properties From Kt Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluid migration pathways are pivotal in enhancing the efficiency and sustainability of geothermal energy extraction. Kolawole et al [44] elucidated the mechanical zonation of rock properties and the development of fluid migration pathways in sedimentary-hosted geothermal reservoirs. Fan et al [45] highlighted the depth of the Curie isotherm and the resistivity of sedimentary caprock as significant factors affecting a geothermal system's performance.…”
Section: Introductionmentioning
confidence: 99%